A Comparative Analysis of Taksimari and Taksinada in Alleviating Pain Following IUD Insertion - Ni Made Risna Sumawati; Pande Putu Indah Purnamayanti; Ni Made Septiari Maryadi (Gema Lingkungan Kesehatan, 2026)
The Intra Uterine Device (IUD) is the best contraceptive for most women but often causes problems, namely pain. Pain can cause physiologic changes such as increased blood pressure, increased heart rate, vasoconstriction (arterial) blood vessels, increased respiratory activity, loss of water, and extreme fatigue. This study aims to determine the comparison of the effectiveness of the use of Five Finger Relaxation Technique (Taksimari with Deep Breath Relaxation Technique (Taksinada) on post-installation pain of the IUD at UPTD Puskesmas Sidemen. The research design used in this study was posttest design with a control group, namely research conducted after treatment (posttest) with two groups of subjects, namely the control group and the treatment group. The sample in the study amounted to 30 respondents with the following criteria: women aged 18-45 years, new IUD acceptors, and IUD installation at Sidemen Community Health Center, 15 respondents were given Taksimari and 15 respondents were given Taksinada. The analysis test used was the Mann Whitney test. The results showed that there were 14 respondents (93.33%) experiencing moderate pain in the Taksimari group, while in the Taksinada group there were 15 respondents (100%) experiencing moderate pain. The results of the bivariate analysis test showed that there was no difference in the effectiveness of non-pharmacological therapy Taksimari with Taksinada with a value of p = 0.317. This study found that there was no difference in the effectiveness of non-pharmacological therapy Taksimari with Taksinada. This study can be used as a basis for consideration in carrying out independent midwifery interventions in pain management.